Service-oriented and cloud computing : 7th IFIP WG 2.14 European Conference, ESOCC 2018, Como, Italy, September 12-14, 2018, Proceedings /: 7th IFIP WG 2.14 European Conference, ESOCC 2018, Como, Italy, September 12-14, 2018, Proceedings. (2018) - Unknown
No abstract available